2004
DOI: 10.1111/j.1467-842x.2004.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in smoking behaviour among young women over life stage transitions

Abstract: Life changes such as marriage and actual or contemplated pregnancy provide opportunities for targeted interventions to help women quit smoking and not relapse after having a baby. Legislation to control smoking on licensed premises would reduce the social pressure on women to smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…Our work suggests that partner status is strongly associated with smoking in both men and women, irrespective of parenthood, which is consistent with findings from other studies (McDermott et al 2004;Waldron and Lye 1989). The provision of social support for quitting smoking and the social control against relapse is usually given as the explanation for the positive effect of marriage on smoking (Klein et al 2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our work suggests that partner status is strongly associated with smoking in both men and women, irrespective of parenthood, which is consistent with findings from other studies (McDermott et al 2004;Waldron and Lye 1989). The provision of social support for quitting smoking and the social control against relapse is usually given as the explanation for the positive effect of marriage on smoking (Klein et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Research on smoking has shown that married people have higher success in quitting smoking than do unmarried people (McDermott et al 2004;Waldron and Lye 1989). The higher smoking cessation rate among married people is usually discussed in the context of the social support provided by marriage (Waldron and Lye 1989) or the development of a more responsible concern with lifestyle and health when living with a partner (Backett and Davison 1995).…”
Section: Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Marriage and parenthood modify smoking behaviour. 28 In the multivariate analysis, marriage was statistically significantly associated with not smoking at both time points, whereas the relationship between not smoking and becoming a parent was evident only for surveys 1 and 2. This may be because of a strong association between parenthood and marriage.…”
Section: Discussionmentioning
confidence: 89%
“…Analysis of differences in sociodemographic and health characteristics between respondents and non-respondents to survey 2 showed that non-respondents were more likely to be smokers, unemployed, have difficulty managing on their available income and have lower levels of education, on the basis of information at survey 1. 28 Thus, non-response may have resulted in underestimation of the prevalence of smoking, and may have decreased the strength of some of the associations that we have reported.…”
Section: Strengths and Limitationsmentioning
confidence: 88%